Financial Reporting Standards and Global Capital Market Integration Processes (gjstudies, 2015)
This paper investigates the complex, non-linear relationship between the adoption of International Financial Reporting Standards (IFRS) and the integration ofglobal capital markets, challenging the prevailing assumption of a direct, positivecausal link. While existing literature predominantly emphasizes harmonization benefits, this research introduces a novel analytical framework that reconceptualizes integration as a multi-dimensional process influenced by institutional complementarities, enforcement heterogeneity, and the interpretive flexibility of accounting standards themselves. Drawing on concepts from institutional theory, network analysis,and the sociology of translation, we argue that the global convergence of reportingstandards does not mechanically produce integrated markets but instead triggersa series of adaptations, translations, and strategic responses by market actors thatcan, paradoxically, reinforce certain forms of fragmentation even as they reduceformal diversity. The methodology employs a mixed-methods design, combining alongitudinal analysis of cross-border equity flows and co-movement patterns across42 jurisdictions from 1995 to 2004 with a qualitative, interpretive analysis of regulatory discourse and corporate narratives surrounding IFRS implementation. Ourfindings reveal three counterintuitive dynamics: first, that mandatory IFRS adoption in jurisdictions with weak enforcement regimes can increase information asymmetry for foreign investors, acting as a temporary barrier to integration; second,that the very flexibility principles within IFRS (e.g., fair value options) can bedeployed to sustain nationally distinct reporting profiles, creating a ’harmonizeddiversity’; and third, that integration is most pronounced not in equity markets perse, but in the secondary market for corporate debt, suggesting that standards affectdifferent asset classes in fundamentally different ways. The study concludes thatthe process of global capital market integration is better understood as a dialecticbetween standardization and differentiation, where accounting standards are notmerely technical instruments but sites of institutional contestation. This reframingoffers original insights for policymakers, standard-setters, and scholars, moving beyond the binary debate of ’adopt versus not adopt’ to consider the conditional andoften unintended consequences of financial reporting harmonization.